Increased Carbohydrate Intake is Associated with Poorer Performance in Verbal Memory and Attention in an APOE Genotype-Dependent Manner - Gardener, S.; Rainey-Smith, S.; Sohrabi, H.; Weinborn, M.; Verdile, Giuseppe; Fernando, W.; Lim, Y.; Harrington, K.; Burnham, S.; Taddei, K.; Masters, C.; Macaulay, S.; et al. (IOS Press, 2017)
Evidence suggests that a diet low in carbohydrates can impact on cognitive performance among those with Alzheimer's disease (AD). However, there is a lack of data assessing this relationship among cognitively normal (CN) older adults at increased future risk of developing AD due to carriage of the apolipoprotein E (APOE) ?4 allele. We assessed the cross-sectional association between carbohydrate intake, cognitive performance, and cerebral amyloid-ß (Aß) load in CN older adults, genotyped for APOE ?4 allele carrier status. Greater carbohydrate intake was associated with poorer performance in verbal memory in APOE ?4 allele non-carriers, and poorer performance in attention in APOE ?4 allele carriers. There were no associations between carbohydrate intake and cerebral Aß load. These results provide support to the idea that decreasing carbohydrate intake may offer neurocognitive benefits, with specific cognitive domains affected in an APOE genotype-dependent manner. These findings warrant further investigation utilizing a longitudinal study design.